AGREEMENT BETWEEN MEASUREMENT OF JUMP HEIGHT IN DIFFERENT VERTICAL JUMP TESTS EXECUTED BY YOUNG FOOTBALL PLAYERS - Marin Gadev; Petar Peev; Oleg Hristov (Scientific Publishing House. NSA Press, 2020)
Football is an intermittent sport with a great number of short and explosive actions. These characteristics of the game require a good level of anaerobic power. The main fi eld tests used as indicators of the development of the anaerobic energy system were the jumps in the vertical plane. The same tests also measured the strength of the lower limbs. We presume that the explosive power of the lower limbs characterizes the development of the alactic anaerobic energy system and strength capacity at the same time. In that case the explosive power of the lower limbs was an important component of the conditioning and strength training of football players. There was a great variety of methods and devices which registered vertical jump height. From this point of view, we wanted to add our study to the research work in the specialized literature. The purpose of this study was to analyze the differences of the jump height measured via two devices. We used the following methods of research: accelerometry, chronometry and statistical analysis. We studied the vertical jump height of 32 football players of the Youth Academy of PFC "Levski"- Sofi a at the age of 13,4. In the research the participants performed three jump tests (squat jump [SJ], counter movement jump [CMJ] and counter movement jump with arm swing [CMJA]) as the jump height was measured via accelerometer and Infrared platform. The results from these two devices were compared via Bland Altman plot and calculation of Intraclass correlation coefficients [ICC]. The results of ICC between the two devices showed very strong correlation of the results for the three tests (SJ (R= .91), CMJ (R= .92) and CMJA (R= .87)). The results of the ANOVA showed statistical difference between the measured jump heights (p< .05 for all test, systematic bias was equal to: SJ=15.6; CMJ=15.2; CMJA= 19.5 and effect size (η2 ) was large SJ= .65; CMJ= .69; CMJA= .65) for the three different types of jump. Conclusions:1) Both of the devices showed good consistency of the collected results; 2) The data collected from the two devices showed significant difference of the jump heights.